2010
DOI: 10.1007/s12029-010-9235-z
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma Presenting as an Incidental Isolated Malignant Portal Vein Thrombosis

Abstract: This unusual case of hepatocellular carcinoma presenting as an incidental malignant portal vein thrombosis without any primary liver lesion is extremely rare. Other reported cases of malignant portal vein thrombosis have been in patients with underlying hepatoma, cirrhosis, or with intrabiliary hepatocelluar carcinoma. In the clinical setting of portal vein thrombosis, imaging studies showing enhancement of the thrombus in the arterial phase are important in leading to the diagnosis of malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…Indeed, PVTT is present in 44% of patients with HCC according to autopsy data and in 31–34% according to clinical data [2]. PVTT can cause partial or total portal vein occlusion and extensive intra- or extrahepatic metastases [3]. Moreover, PVTT in the main portal trunk puts pressure on the portal vein, which would further lead to gastrointestinal bleeding and ascites and induce multiple intrahepatic tumor dissemination and recurrence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, PVTT is present in 44% of patients with HCC according to autopsy data and in 31–34% according to clinical data [2]. PVTT can cause partial or total portal vein occlusion and extensive intra- or extrahepatic metastases [3]. Moreover, PVTT in the main portal trunk puts pressure on the portal vein, which would further lead to gastrointestinal bleeding and ascites and induce multiple intrahepatic tumor dissemination and recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…The median survival of patients with HCC and PVTT is 2.7–4.0 months, whereas survival in patients with HCC but without PVTT is 24.4 months [57]. For these patients, there is no effective treatment and the optimal treatment remains controversial [3]. Most HCCs with PVTT are technically unresectable and they are not suitable for curative therapies.…”
Section: Introductionmentioning
confidence: 99%
“…A few case reports have described SVT as the first sign of liver and pancreatic malignancies. [7][8][9] A meta-analysis of 32 studies, each including between 10 and 237 patients with portal or hepatic vein thrombosis (HVT), showed that thrombosis often occurred prior to diagnosis of myeloproliferative neoplasms. 10 The association between SVT and subsequent cancer risk has never been studied in a population-based setting using a comparison cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Одной из основных локальных причин развития тромбозов в висцеральном венозном бассейне (от 4 до 16%) являются онкологические заболевания органов брюшной полости, при этом венозный тромбоз служит, как правило, его первым признаком [30,73]. В ряде работ именно на тромбоз висцеральных вен указывают как на первое проявление гепатоцеллюлярного рака и рака поджелудочной железы [51,59,62,66,76].…”
Section: этиологияunclassified